Critical Thinking Abilities of Prospective Mathematics Teachers Based on Learning Styles - Rina Dwi Setyawati; Budi Waluya; Isnarto; Putriaji Hendikawati (Hipotenusa: Journal of Mathematical Society, 2025)
This research attempts to describe the critical thinking abilities of prospective fifth-semester mathematics education teachers at PGRI University Semarang through a qualitative approach. The researcher, as the primary instrument, employed a learning style questionnaire, a Group  Theory  critical thinking test, and an interview guide with purposively selected subjects. Data were analyzed through flow diagrams which included data reduction, data presentation, and drawing conclusions. Data credibility is obtained through triangulation of sources and time. The research result show that the average critical thinking ability test for visual and audotory styles is relatively higher than for kinsestetic learners. At the stages of focus, reasoning, and inference, all three stylesthe stages of saturation, clarity, and overview, a clear distinction emerges, with the visual style demonstrating greater effectiveness by producing answer that are both accurate and complete, unlike the auditory and kinesthetic counterparts. The ability of the three learning styles to express valid arguments to clarify the truth of the answers they make is still very low. Providing training with open-ended problem-based questions and problem-based learning as well as honing the arguments of prospective mathematics teachers are the alternative solutions chosen to improve critical thinking skills.